2019
DOI: 10.1186/s12886-019-1079-0
|View full text |Cite
|
Sign up to set email alerts
|

Performance of femtosecond laser-assisted cataract surgery in Chinese patients with cataract: a prospective, multicenter, registry study

Abstract: BackgroundThis study aimed to investigate the completion rate, visual performance, and adverse outcomes of femtosecond laser-assisted cataract surgery (FLACS) in Chinese patients.MethodsThis is a prospective, single-arm, multicenter registry study of 19 cataract surgery clinics in China. Chinese patients with cataract who underwent FLACS using the Alcon LenSx® laser system in single eye (n = 1140) or both eyes (n = 201) were enrolled and data were collected between March 2015 and August 2016. Clinical characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Tissue injuries such as endothelial cell loss and macular edema are frequently induced during surgery (22). Previous studies have reported that the use of FLACS has fewer complications and is more reliable compared with CPCS (23). The present results suggested that there was no difference in CDVA, as well as aqueous flare, between CPCS groups and FLACS groups.…”
Section: Discussionsupporting
confidence: 52%
“…Tissue injuries such as endothelial cell loss and macular edema are frequently induced during surgery (22). Previous studies have reported that the use of FLACS has fewer complications and is more reliable compared with CPCS (23). The present results suggested that there was no difference in CDVA, as well as aqueous flare, between CPCS groups and FLACS groups.…”
Section: Discussionsupporting
confidence: 52%
“…The result, which indicated that there was a higher ratio of cataract patients under 70 years of age currently than there was 10 years ago, was statistically significant (χ 2 = 199.008, P < 0.001). Over the last 10 years, the development of phacoemulsification and femtosecond laser-assisted cataract surgery [ 13 , 14 ] and the popularity of functional intraocular lenses [ 15 , 16 ] have advanced cataract surgery in China, leading to better visual outcomes. Urban Chinese cataract patients in the present study tended to choose surgical treatment earlier than cataract patients did 10 years ago, a decision which could improve their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…However, we should not forget the fact that complications such as vitreous loss might be reduced with FLACS [17] and therefore, its complications should not be overestimated but instead, we should also pay attention to its beneficial features. Also, FLACS using the LenSx laser system might achieve better results in a real world setting [18].…”
Section: Discussionmentioning
confidence: 99%